2018
DOI: 10.1071/rd17157
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune genes in persistent mating-induced endometritis in horses

Abstract: Persistent mating-induced endometritis (PMIE) severely decreases fertility in horses. The aim of the present study was to evaluate differences between horses susceptible to PMIE and a control group in terms of the expression of selected immune response and effector genes, and the effects of oestrous cycle stage on this expression. Endometrial biopsies from 18 uterine samples of mares in the control group (eight in dioestrus, 10 in oestrus) and 16 PMIE-susceptible mares (four in dioestrus, 12 in oestrus) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 40 publications
2
33
1
Order By: Relevance
“…In agreement with other studies (Crossett, Allen, & Stewart, ; Hayes et al, ), P19/uterocalin (also known as concepticalin, equicalin and lipocalin P19) was found to be more abundant in endometrial flush fluid samples from mares in dioestrus. Studies on endometrial mRNA expression of uterocalin in mares have also indicated greater expression in dioestrus than in oestrus (Marth et al, ). Uterocalin is a P 4 ‐dependent protein that is secreted by endometrial glands both in dioestrus and early pregnancy (Crossett et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with other studies (Crossett, Allen, & Stewart, ; Hayes et al, ), P19/uterocalin (also known as concepticalin, equicalin and lipocalin P19) was found to be more abundant in endometrial flush fluid samples from mares in dioestrus. Studies on endometrial mRNA expression of uterocalin in mares have also indicated greater expression in dioestrus than in oestrus (Marth et al, ). Uterocalin is a P 4 ‐dependent protein that is secreted by endometrial glands both in dioestrus and early pregnancy (Crossett et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…have also indicated greater expression in dioestrus than in oestrus (Marth et al, 2016(Marth et al, , 2018. Uterocalin is a P 4 -dependent protein that is secreted by endometrial glands both in dioestrus and early pregnancy (Crossett et al, 1996).…”
Section: Studies On Endometrial Mrna Expression Of Uterocalin In Maresmentioning
confidence: 99%
“…Adaptive immunity responds selectively and gradually to the detection of antigens, and this is mediated by the T lymphocytes [95]. In contrast, the response to breeding is dictated by the innate immune response [28,30]. This consists of a non-specific, rapid, and transient response [96].…”
Section: Non-infectious Endometritismentioning
confidence: 99%
“…The local innate immune response is immediately activated after antigen recognition and signaling by mucosal epithelial cells in the endometrium [28,30]. The detection of foreign particles induces the activation of the innate immune system, which is the first line of defense.…”
Section: Innate Immune Response To Endometritismentioning
confidence: 99%
See 1 more Smart Citation